The Modern Brick Vernacular in Northern Europe : Austria, Germany, and Holland 1914-1935 (GA Document Special Issue)
Se aborda de forma teórica el periodo histórico comprendido entre 1914-1935 a partir del análisis de obras significativas. Contiene: 1913-1940 Peter Vilhelm Jensen-Klint : Grandtvigs Church, Copenhagen, Denmark. 1919-21 Mies van der Rohe : Friedrichstrasse Office Building and the Glass Skyscraper. 1912-22 Pieter Lodewijk Kramer : De Dageraad Housing Amsterdam, Holland. 1920 Erich Mendelsohn : Einstein Tower, Postdam, Germany. 1920 Vladimir Tatlin :Monument to the Third International. 1920-21 Michel de Klerk : Apartment Blocks, Henriette Ronnerplein, Amsterdam, Holland. 1920-24 Peter Behrens : Administrative Building, L. G. Farben (Hoechst) Dyeworks, Frankfurt am Main, Germany. 1920-28 Erik Gunnar Asplund : Stokholm Publica Library, Stocholm, Sweden. 1920-35 Hendrik Petrus Berlage : Gemeentemuseum, (Municipal Museum), The Hague, Holland. 1922 Eliel Saarinen : Chicago Tribune Tower Competition. 1922 Albert Kahn : Rouge River Glass Plant, Ford Motor Company, Dearborn, Michigan, U.S.A. 1922-23 Auguste Perret : Notre-Dame du Raincy, Le Raincy, France. 1923 Frank Lloyd Wright : La Miniatura, Millard House, Pasdena, California, U.S.A. 1923 Fritz Höger : Chilehaus, Shipping Headquarters, Hamburg, Germany. 1923-24 Le Corbusier : La Rovhe-Jeanneret, Double-House, Paris, France. 1923-24 Gerrit Rietveld : The Schröder House, Unrecht, Holland. 1923-24 Hugo Häring : Gut Garkau Agricultural Building, Near Lübeck, Germany. 1923-24 Henri Sauvage, Charles Sarazin : Flats, rue des Amiraux, Paris, France. 1924-31 Willem Marinus Dudok : Town Hall, Hilversum, Holland. 1925 Le Corbusier : Pavillion de l’Espirit Nouveau, Exposition des Arts Décoratifs, Paris, France.